THE ROLE OF STRATEGIC LEADERSHIP PRACTICES IN BUILDING INDEPENDENT ORGANIZATIONS: AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF WORKERS IN IRAQI PRIVATE BANKS - Adnan Rashed Awad; Hashm Rashad ahrash; Abd alfatah Hasan Soltan (American Journals, 2023)
The study aimed to study the role of strategic leadership practices in building independent organizations: an exploratory study of the opinions of a sample of workers in Iraqi private banks. To achieve the objectives of this study, the researcher prepared a questionnaire to measure the study variables on some of them. The questionnaire tool was distributed to the study sample, where the final number that was analyzed reached (98) questionnaires. The study reached several results, the most important of which was: (There is a statistical effect of the level of ability to acquire scarce resources in building independent organizations from the point of view of workers in Iraqi private banks. There is a statistical impact on the level of ability to deal with strategic decisions from the point of view of workers in Iraqi private banks, and There is a statistical effect of the level of possibility of expanding relations with influencers from the point of view of workers in Iraqi private banks. The study concluded with a set of recommendations, the most important of which was the necessity of strategic leadership studies related to the role of practices building organizations, and Building strategic leadership practices based on the analysis of the internal and external environments to identify opportunities in the external environment
Keywords: strategic leadership practices, building independent organizations, Iraqi private banks.